Microbiology Essentials and Applications - McKane, Larry Kandel, Judy (McGraw-Hill, 1996)
This edition provides students with the fundamentals of microbiology, taking full advantage of a variety of modern pedagogical techniques. The text also covers applications of microbiology to clinical, environmental, industrial and food microbiology.